The Utility of a Preoperative Clinic Questionnaire to Predict Postoperative Delirium Risk - Jaffer, Amir K.; Michota, Franklin A.; Bader, Angela M.; Borkowski, Raymond; Kroen, Collin; Harte, Brian; Gugliotti, David; Hepner, David; Correll, Darin; Ho, Thomas; Bludau, Juergen; Santos, Jhoanna; et al. (Cleveland Clinic Journal of Medicine, 2007)
300 Multiple ChoicesThis is a pdf-only article and there is no markup to show you.full-text.pdf